Assembly and activation of the Hippo signalome by FAT1 tumor suppressor - Martin, Daniel; Degese, Maria S.; Vitale-Cross, Lynn; Iglesias-Bartolome, Ramiro; Valera, Juan Luis Callejas; Wang, Zhiyong; Feng, Xiaodong; Yeerna, Huwate; Vadmal, Vachan; Moroishi, Toshiro; Thorne, Rick F.; Zaida, Moraima; et al. (Nature Research, 2018)
Dysregulation of the Hippo signaling pathway and the consequent YAP1 activation is a frequent event in human malignancies, yet the underlying molecular mechanisms are still poorly understood. A pancancer analysis of core Hippo kinases and their candidate regulating molecules revealed few alterations in the canonical Hippo pathway, but very frequent genetic alterations in the FAT family of atypical cadherins. By focusing on head and neck squamous cell carcinoma (HNSCC), which displays frequent FAT1 alterations (29.8%), we provide evidence that FAT1 functional loss results in YAP1 activation. Mechanistically, we found that FAT1 assembles a multimeric Hippo signaling complex (signalome), resulting in activation of core Hippo kinases by TAOKs and consequent YAP1 inactivation. We also show that unrestrained YAP1 acts as an oncogenic driver in HNSCC, and that targeting YAP1 may represent an attractive precision therapeutic option for cancers harboring genomic alterations in the FAT1 tumor suppressor genes.